2013
DOI: 10.1371/journal.pone.0081030
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling Promotes Early Hematopoietic Progenitor Formation and Erythroid Specification during Embryonic Stem Cell Differentiation

Abstract: The generation of hematopoietic stem cells (HSCs) during development is a complex process linked to morphogenic signals. Understanding this process is important for regenerative medicine applications that require in vitro production of HSC. In this study we investigated the effects of canonical Wnt/β-catenin signaling during early embryonic differentiation and hematopoietic specification using an embryonic stem cell system. Our data clearly demonstrates that following early differentiation induction, canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 77 publications
(103 reference statements)
0
24
0
1
Order By: Relevance
“…The underlying mechanism to account for this defect has not been elucidated thus far. Nevertheless, it has recently been reported that pharmacological activation of the canonical WNT signaling by the GSK-3b inhibitor LiCl primes undifferentiated MSCs toward osteoblastic lineage [32]. In view of this observation and provided that in MDS-derived MSCs the canonical WNT signaling is downregulated, we hypothesized that the reduced osteoblastic lineage priming of patient MDSs might be attributed, at least in part, to the impaired canonical WNT signaling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The underlying mechanism to account for this defect has not been elucidated thus far. Nevertheless, it has recently been reported that pharmacological activation of the canonical WNT signaling by the GSK-3b inhibitor LiCl primes undifferentiated MSCs toward osteoblastic lineage [32]. In view of this observation and provided that in MDS-derived MSCs the canonical WNT signaling is downregulated, we hypothesized that the reduced osteoblastic lineage priming of patient MDSs might be attributed, at least in part, to the impaired canonical WNT signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of canonical WNT signaling by the GSG-3b inhibitor LiCl has been shown to prime undifferentiated MSCs toward the osteoblastic lineage [32]. In view of this observation and provided that in MDS-derived MSCs the canonical WNT signaling is downregulated, we investigated whether the reduced osteoblastic lineage priming of MDSderived MSCs might be attributed, at least in part, to the impaired canonical WNT signaling.…”
Section: Pharmacological Activation Of Canonical Wnt Signaling In Mdsmentioning
confidence: 99%
“…(P)RR and v-ATPase were shown to be required to mediate Wnt signaling during antero-posterior patterning of Xenopus early central nervous system development. There has been accumulating evidence which shows the close relationship among iron, the Wnt signaling and erythropoiesis (Brookes et al 2008;Tarafdar et al 2013). Canonical Wnt/β-catenin signaling plays important roles in mesodermal specification, primitive erythropoiesis and early hematopoietic progenitor formation during hematopoietic induction (Tarafdar et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There has been accumulating evidence which shows the close relationship among iron, the Wnt signaling and erythropoiesis (Brookes et al 2008;Tarafdar et al 2013). Canonical Wnt/β-catenin signaling plays important roles in mesodermal specification, primitive erythropoiesis and early hematopoietic progenitor formation during hematopoietic induction (Tarafdar et al 2013). Brookes et al (2008) speculated that iron-medicated Wnt signaling and c-myc induced expression of transferrin receptor 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation